E-commerce legislation in some countries - lessons for Vietnam - Le, Ho Trung Hieu; Vu, Thi Bich Hai (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
E-commerce is a key factor in the globalization process, serving as a significant driver for economic development. Transparent conduct of e-commerce is a crucial condition for fostering a healthy economic environment and enhancing the competitiveness of businesses. Despite being widespread globally, the legal regulation of e-commerce in Vietnam remains an area that requires continuous improvement. This article examines the e-commerce laws of leading countries such as China and the United States, aiming to draw lessons and experiences for Vietnam to enhance its legal framework for e-commerce in the current context.